P252 A retrospective evaluation of the diagnostic utility of adenosine deaminase in pleural tuberculosis in a low-prevalence area. (12th November 2015) - Marples, L; Sivakumar, P; Breen, R; Ahmed, L
Abstract : Introduction and objectives: Pleural fluid adenosine deaminase (pfADA) is a validated diagnostic marker for pleural tuberculosis (TB) in high prevalence areas, with good sensitivity and specificity reported at a threshold of 40 U/L. However, in north-west Europe pfADA is not routinely measured, due to a lack of evidence as to its diagnostic utility in areas of low TB prevalence. The aim of this study is to assess the sensitivity and specificity of pfADA in a low-prevalence area, evaluating its diagnostic value for pleural TB. Methods: A retrospective analysis considered all pfADA-tested suspected pleural TB patients within one hospital trust from 2009–2015. This cohort was then divided into two groups: those with a confirmed diagnosis of pleural TB and those without pleural TB. Those without pleural TB were used as a control group, to determine the sensitivity and specificity of pfADA at various thresholds. Results: Of 156 patients tested for pfADA, 25 had confirmed pleural TB and 131 did not, with mean pfADA levels of 71.7 (±25.2) and 19.8 (±22.4), respectively. On a Receiver Operating Characteristic (ROC) curve (Figure 1 ), pfADA of 30 U/L has a sensitivity of 100%, specificity 83%, positive and negative predictive values of 53% and 100% respectively. At a threshold of 40 U/L, sensitivity was 88% with a specificity of 88%. The calculated area under ROC curve is 0.949 (95% CI 0.91–0.982). Conclusion: Although the positive predictive value of pfADA may be lower in areas of low TB prevalence, its negative predictive value is unaffected, retaining its value as a worthy screening test to exclude pleural TB, allowing focus on obtaining adequate culture samples and biopsies in suspected pleural TB.